2018
DOI: 10.1108/jeee-10-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of an entrepreneurship training program in Recife, Brazil

Abstract: Purpose The purpose of this paper is to understand in a qualitative context, the importance of the EMPRETEC entrepreneurship training in an emerging country context of Brazil. This helps to understand the capacity of entrepreneurship education to improve the ability of individuals to generate new business opportunities. Design/methodology/approach The data were collected through three semi-structured interview scripts and analyzed with the support of the NVIVO qualitative analysis software using Bardin conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Additionally, some enterprises from these groups sell their products to the local governments. Such initiatives are in line with the literature that has reinforced the relevance of increasing the capabilities of BOP entrepreneurs (Coelho et al, 2018;Jard on and Tañski, 2018) to support their innovation capacity (Karnani, 2009). However, in these groups, dynamic capabilities were not observed.…”
Section: Contributions To the Literaturesupporting
confidence: 77%
“…Additionally, some enterprises from these groups sell their products to the local governments. Such initiatives are in line with the literature that has reinforced the relevance of increasing the capabilities of BOP entrepreneurs (Coelho et al, 2018;Jard on and Tañski, 2018) to support their innovation capacity (Karnani, 2009). However, in these groups, dynamic capabilities were not observed.…”
Section: Contributions To the Literaturesupporting
confidence: 77%
“…However, the approach has become popular in 2018, as there is an urge from the Ministry of Higher Education to increase the quality of learning [37] [38]. Besides, many research findings have identified the benefits of heutagogy practice, such as skills, engagement, self-reflect, and self-motivation among the students, are essential skills needed to survive in the 4IR challenges [39][40][41][42]. The changes role of educators is also one of the strengths of heutagogy [29] [38].…”
Section: 1mentioning
confidence: 99%
“…This is aligned with findings obtained by Ismail (2018) that stated the entrepreneurship training give an impact on business knowledge and practices. Thus, entrepreneurship training is important in influencing entrepreneurs to improve their abilities and able to seek business opportunities (Coelho et al, 2018)..…”
Section: Literature Review Entrepreneurship Trainingmentioning
confidence: 99%
“…Various government and private agencies provide training for entrepreneurs in different sectors. The purpose of the entrepreneurship training program is to equip entrepreneurs with crucial skills and provide guidance in order to for them to give positive output in terms of their enterprise's profitability (Coelho, Marques, Loureiro, & Ratten, 2018).. Commonly, most of entrepreneurship training programs contribute to a positive impact on entrepreneurs such as an increase in skills, knowledge and enterprise performance (Warhuus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%